Shifting the Balance: How Top-Down and Bottom-Up Input Modulate Pain via the Rostral Ventromedial Medulla - Chen, Qiliang; Heinricher, Mary M. (Frontiers in Pain Research, 2022)
The sensory experience of pain depends not only on the transmission of noxious information (nociception), but on the state of the body in a biological, psychological, and social milieu. A brainstem pain-modulating system with its output node in the rostral ventromedial medulla (RVM) can regulate the threshold and gain for nociceptive transmission. This review considers how RVM pain-modulating neurons, ON-cells and OFF-cells, are engaged by “top-down” cognitive and emotional factors, and by “bottom-up” sensory inputs, to enhance or suppress pain.